Role of “Second Look” Lymph Node Search in Harvesting Optimal Number of Lymph Nodes for Staging of Colorectal Carcinoma - Ameer Hamza; Ramen Sakhi; Sidrah Khawar; Ahmed Alrajjal; Jacob Edens; Muhammad Siddique Khurram; Uqba Khan; Susanna Szpunar; Paul Mazzara (Gastroenterology Research and Practice)
As with other malignancies, lymph node metastasis is an important staging element and prognostic factor in colorectal carcinomas. The number of involved lymph nodes is directly related to decreased 5-year overall survival for all pT stages according to United States Surveillance, Epidemiology, and End Results (SEER) cancer registry database. The National Quality Forum specifies that the presence of at least 12 lymph nodes in a surgical resection is one of the key quality measures for the evaluation of colorectal cancer. Therefore, the harvesting of a minimum of twelve lymph nodes is the most widely accepted standard for evaluating colorectal cancer. Since this is an accepted quality standard, a second attempt at lymph node dissection in the gross specimen is often performed when the initial lymph node count is less than 12, incurring a delay in reporting and additional expense. However, this is an arbitrary number and not based on any hard scientific evidence. We decided to investigate whether the additional effort and expense of submitting additional lymph nodes had any effect on pathologic lymph node staging (pN). We identified a total of 99 colectomies for colorectal cancer in which the prosector subsequently submitted additional lymph nodes following initial review. The mean lymph node count increased from 8.3 ± 7.5 on initial search to 14.6 ± 8.0 following submission of additional sections. The number of cases meeting the target of 12 lymph nodes increased from 14 to 69. Examination of the additional lymph nodes resulted in pathologic upstaging (pN) of five cases. Gross reexamination and submission of additional lymph nodes may provide more accurate staging in a limited number of cases. Whether exhaustive submission of mesenteric fat or fat-clearing methods is justified will need to be further investigated.